Proximal Tibial Bone Harvesting Under Local Anesthesia Without Intravenous Sedation in the Dental Office: A Case Report - Chun-Ming Chen (Kaohsiung Journal of Medical Sciences, 2008)
Maxillary sinus enlargement often occurs in the maxillary posterior edentulous area and reduces the available bone height for implantation. Therefore, maxillary sinus lift and bone graft procedures are necessary to provide sufficient available bone. Autogenous bone grafting is the best base for implant osseointegration. Recently, tibial bone has been recognized as an alternative extraoral donor site. We present a case in which we used a proximal tibia bone graft for maxillary sinus augmentation under local anesthesia without sedation in the dental office. During a 4-year postoperative follow-up, gait was not disturbed and the scar on the donor site remained unremarkable.